Virtual learning environments: major trends in the use of modern digital technologies in higher education institutions - Mariana Kovtoniuk; Olena Kosovets; Olena Soia; Lyubov Tyutyun (Academy of Cognitive and Natural Sciences, 2022)
The article reveals the features of development and integrated implementation of virtual learning environment with the use of modern digital technologies in the learning process of higher education. The article summarizes the interpretation of the concept of "virtual learning environment". Virtual learning environment can be interpreted as an immersive online learning environment that has a methodologically integrated learning system, provides an open interactive dynamic learning process in cyberspace using modern digital technologies that take into account the individual educational characteristics of students. The main subjects and functions of the virtual learning environment are identified. One of the links in creating a virtual learning environment is the development of free learning space through websites. It is stated that the teacher's site should be integrated into the learning technology designed and implemented by the teacher. Then the logic and structure of the lesson will be an element of the teacher's creativity, and he is able to choose his own strategy and teaching methods, and not just follow the presentation of the material proposed by other authors. In conditions when the idea of personality-oriented learning, built on the innovative activities of the teacher, is fundamental in education, this approach, according to our research, is crucial. The possibilities of modern network technologies involved in the content management system are described, the roles of participants in the educational process are determined, the tasks solved by educational platforms are indicated, their main functions in the learning environment of higher education institutions are described.